Research on Improving the Working Current of NbOx-Based Selector by Inserting a Ti Layer - Liu, Chunlei; Ma, Guokun; Zeng, Junpeng; Tan, Qiuyang; Zhang, Ziqi; Chen, Ao; Liu, Nengfan; Wan, Houzhao; Wang, Baoyuan; Tao, Li; Rao, Yiheng; Shen, Liangping; et al. (Frontiers in Materials, 2021)
To achieve the highest possible integration storage density in the V-point structure, the working current of the selector in the one-selection one-resistance (1S1R) structure should match with the Resistance Random Access Memory (RRAM). In this study, a selector device is designed with Ti/NbOx/Ti/Pt structure through the magnetron sputtering method and achieves excellent performance of threshold switching under ultra-large Compliance Current (CC) up to 100 mA. Furthermore, both the switching voltages and the OFF state resistance of the device demonstrate excellent stability even when CC is increased to milliampere level, attributed from the existence of metallic NbO in the switching layer. This work provides evidence that Ti/NbOx/Ti/Pt device has a great potential to drive RRAM in the V-point structure.